Precipitable Water Vapor Conditions for Infrared Observations at Korean Astronomical Observatories - Sungho Lee (Journal of Astronomy and Space Sciences, 2007)
KASINICS (Korea Astronomy and Space Science Institute Near Infrared Camera System) is equipped with a InSb array which can observe 1--5~μm bands in near-infrared. The absorption and emission by telluric water vapor becomes serious in the bands longer than 3~μm. We measured PWV (Precipitable Water Vapor) levels above Bohyusan Optical Astronomy Observatory and Sobaeksan Optical Astronomy Observatory from July 2006 to August 2007 using the GPS PWV measurement system of KASI. We found that monthly averaged PWVs are lower than the prediction using dew-point temperature and as low as above Kitt Peak from September to February.